Analysis of the Relationship between Accounting Profit and Cash Flow Components with Stock Prices: Analisis Hubungan Laba Akuntansi dan Komponen Arus Kas Dengan Harga Saham - Fitri Nurani; Andrianto (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine the relationship between accounting profit, operating cash flow, investment cash flow and financing cash flow with stock prices. This study uses data from the financial statements of companies listed in LQ 45 on the Indonesian Stock Exchange from 2014- 2019. And the company sampling technique using purposive sampling a number of 34 companies LQ45 in 2014-2019. The research sample was tested using Pearson Correlations analysis and normality test and linearity test. The results of the Pearson Correlations correlation analysis show that the variables of accounting earnings and funding cash flows have a relationship with stock prices with a significance value of <0.05. And the operating cash flow and investment cash flow variables have no relationship with stock prices with a significance value of ≥ 0.05